Specification of floral reproductive organs : the role of AGAMOUS - Ó Maoiléidigh, Diarmuid Seosamh (Trinity College (Dublin, Ireland). Department of Genetics, 2012)
Homeosis is referred to as the transformation of an organ's identity toward the identity of another organ. This term was coined in 1894 and soon thereafter; these organ transformations were attributed to the variation in certain genes. These genes became known as "homeotic" genes and examples were highlighted in several model organisms including Drosophila melanogaster and Arabidopsis thaliana. In Arahidopsis, the first of these homeotic genes was cloned in 1990, and it was named AGAMOUS (AG), as plants without a functional copy of this gene do not develop reproductive organs.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin.